2008
DOI: 10.1063/1.2836798
|View full text |Cite
|
Sign up to set email alerts
|

The local environment of Co in B5CHx

Abstract: Cobalt-doped boron carbides produced by simultaneous plasma-enhanced chemical vapor deposition of carborane and cobaltocene are investigated. Cobalt does not dope plasma-enhanced chemical vapor deposition grown boron carbides as a random fragment of the cobaltocene source gas. The Co atoms are fivefold boron coordinated ͑R = 2.1 Å͒ and chemically bonded to the icosahedral cages of B 10 CH x or B 9 C 2 H y . Pairwise Co doping occurs with the cobalt atoms favoring sites about 5.3 Å apart. The cobalt strongly hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Monochromatic light was obtained by using a double crystal monochromator of Lemonnier type [18], equipped with Ge(220) crystal pair and the overall resolution was ~ 2 eV. The EXAFS and XANES spectra were collected in the fluorescent yield mode, as has proven to be successful in characterizing other doped boron carbides [6,19,20].…”
Section: Methodsmentioning
confidence: 99%
“…Monochromatic light was obtained by using a double crystal monochromator of Lemonnier type [18], equipped with Ge(220) crystal pair and the overall resolution was ~ 2 eV. The EXAFS and XANES spectra were collected in the fluorescent yield mode, as has proven to be successful in characterizing other doped boron carbides [6,19,20].…”
Section: Methodsmentioning
confidence: 99%
“…The local structure of the cobalt doped semiconducting boron carbide has been determined by extended x-ray absorption fine structure (EXAFS) and x-ray absorption near edge structure (XANES) spectroscopies [22,26] and to some extent in model cluster calculations [27]. Application of XANES and EXAFS techniques to determine the local structure of the undoped boron carbides has not been successful likely due to the low boron and carbon K-shell x-ray cross-sections [28,29], although the extended electron energy loss fine structure has proved to be a comparatively useful technique [30].…”
Section: Introductionmentioning
confidence: 99%
“…Relatively extended orbitals of this type occur in some oxides 16 and Co-doped semiconducting boron carbides. [7][8][9] To gauge the usefulness of the present material for spinelectronics applications, we have fabricated Cr-DLC heterojunctions with silicon. We consider chromium a p-type dopant of diamond-like materials, which is supported by our ability to make good heterojunction diodes with n-type silicon.…”
Section: Magnetic and Transport Propertiesmentioning
confidence: 99%
“…15 In these structures, which are of interest in optics and spin electronics, the carbon 2p electrons play a role similar to oxygen 2p electrons in oxides 16 and to boron 2p electrons in Co-doped boron carbide. [7][8][9] Our focus is on Cr-doped hydrogenated diamondlike carbon ͑Cr-DLC͒ and chromium carbide hydrogenated DLC alloys, which we investigate as a mixed matrix material and in the form of heterojunctions for spin-electronics applications. Previous research on similar system indicates that clustering of chromium impurities is expected for concentrations exceeding about 1.5%, 17 although Fan et al 18 reported uniform Cr distribution in C matrix at lower levels ͑about 6 at.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation